NILAI-NILAI PERJUANGAN TOKOH DALAM NOVEL DOMPET AYAH SEPATU IBU KARYA J.S KHAIREN - Ririn Fatmala; Sumiman Udu; La Ode Balawa (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The aim of this research is to describe the values of the characters' struggles and reveal the story in the novel Dompet Ayah Shoes Ibu by J.S Khairen. The benefit of this research is that it provides readers with an understanding to always be active in reading and understanding the values of struggle displayed in literary works. The data used in this research is the novel Dompet Ayah Shoes Ibu by J.S Khaien. The data source in this research is the novel Dompet Ayah Shoes Ibu by J.S Khairen. The data collection technique in this research uses a sociological approach to literary works, which is to question the content and objectives as well as things implied in the literary work itself and is related to social problems and what the purpose or message is to be conveyed. The results of this research describe (1) the value of being willing to sacrifice (2) the value of unity (3) the value of respect (4) the value of cooperation (5) the value of patience and the spirit of never giving up. The form of data from the research is in the form of several sentences or texts containing the value of the struggle of the characters in the novel Dompet Ayah Shoes Ibu being studie